PENGARUH PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA TERHADAP PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN - Yuliana, Ema; Handayani, Tutut; Fahmi, Fahmi; Murtopo, Ali (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study is entitled “The Effect of Differentiated Learning Models in the Merdeka Curriculum on the Cognitive Development of 5-6 Year Old Children”. The problem addressed in this study is the low level of cognitive development in children. This study aims to determine whether there is an effect of the Differentiated Learning Model in the Merdeka Curriculum on the Cognitive Development of 5-6 Year Old Children. This study is a pre-experimental study with a one-group pre-test-post-test design. The sample in this study consisted of 15 children, comprising 9 boys and 6 girls. The data collection techniques used in this study were observation, testing, and documenta tion. The data analysis techniques used in this study were normality test, homogeneity test, and hypothesis test. The hypothesis results were obtained after conducting a pretest and posttest, then the researcher analyzed the research results. The data analysis results showed that there was a significant effect, as evidenced by the t-count > t-table, so Ha was accepted and Ho was rejected, which means that there was a significant effect of the use of the Differentiated Learning Model in the Curriculum on the Cognitive Development of 5-6 Year Old Children.